1996
DOI: 10.2139/ssrn.451
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants and Consequences of Financial Education in the Workplace: Evidence from a Survey of Households

Abstract: In recent years, the United States has witnessed significant growth in programs of financial and retirement education in the workplace. This phenomenon provides an opportunity to assess the effects of targeted education programs on financial choices. This paper uses a novel household survey to develop econometric evidence on the efficacy of employer-based financial education.While our primary focus concerns the effects of these programs on saving (both in general and for the purposes of retirement), we also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 5 publications
1
49
0
1
Order By: Relevance
“…Bernheim and Garrett in their study showed that saving rates increase with education, at the same time the study emphasized that low-income individuals have less access to financial education (Bernheim & Garrett, 1996). Other studies, for instance, by Bernheim and Ng suggest that most Americans have relatively limited financial knowledge (Bernheim, 1995;Ng, 1992).…”
Section: Savings In Rural Areasmentioning
confidence: 93%
“…Bernheim and Garrett in their study showed that saving rates increase with education, at the same time the study emphasized that low-income individuals have less access to financial education (Bernheim & Garrett, 1996). Other studies, for instance, by Bernheim and Ng suggest that most Americans have relatively limited financial knowledge (Bernheim, 1995;Ng, 1992).…”
Section: Savings In Rural Areasmentioning
confidence: 93%
“…Bernheim and others on the importance of investor education (Bernheim, 1997;Bernheim and Garrett, 1996). This paper is also related to the more narrowly-defined economic research on 401(k) plans.…”
Section: Ties To the Previous Literature On Savingsmentioning
confidence: 96%
“…On the contrary, there are several reasons to suspect that eligibility would be significantly correlated with the underlying predisposition to save (Bernheim, 1994c, Engen, Gale, andScholz, 1994 and non-eligibles are often several times as large as 401(k) balances for eligibles (see also Engen, Gale, and Scholz, 1994). Using a more recent cross-sectional household survey sponsored by Merrill Lynch, Bernheim and Garrett (1995) corroborate this finding. Thus, unless one believes that 401(k)s crowd-in other forms of saving at the rate of four or five to one, the evidence must be construed as indicating that eligibility is strongly correlated with the innate inclination to save.…”
Section: Exploiting Exogenous Variation In Eligibilitymentioning
confidence: 87%
“…Bernheim and Garrett (1995) implement this strategy using the Merrill Lynch household survey data, which contains self-reported measures of flow saving (expressed as fractions of income), as well as categories of wealth. They find that 401(k) eligibility is associated with an increase in the retirement saving rate that exceeds the corresponding increase in the overall rate of saving.…”
Section: Exploiting Exogenous Variation In Eligibilitymentioning
confidence: 99%
See 1 more Smart Citation